Development of Transparent and Opaque Vacuum Insulation Panels for Energy Efficient Buildings. (November 2015) - Kucukpinar, Esra; Miesbauer, Oliver; Carmi, Yoash; Fricke, Marc; Gullberg, Leif; Erkey, Can; Caps, Roland; Rochefort, Malcolm; Moreno, Araceli Galvez; Delgado, Clara; Koehl, Michael; Holdsworth, Paul; et al.
Abstract: One reason for heat losses in buildings is inadequate insulation. Vacuum Insulation Panels (VIPs) is emerging as a promising solution, being more energy efficient than conventional insulation materials, thinner and lighter. A VIP is made by placing a core insulation material inside a gas-barrier envelope and evacuating the air from inside the panel. The limitations to wide-scale VIP commercialization lie in lack of low-cost and high-volume processes to turn them into products suitable for use in buildings, and their short in-service lifetimes. These drawbacks were researched in a European funded project "NanoInsulate", and this paper gives an overview of results.